2009
DOI: 10.1038/embor.2009.24
|View full text |Cite
|
Sign up to set email alerts
|

Human U1 snRNA forms a new chromatin‐associated snRNP with TAF15

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits distribution, and reproduction in any medium, provided the original author and source are credited. This license does not permit commercial exploitation without specific permission.The U1 small nuclear RNA (snRNA)-in the form of the U1 spliceosomal Sm small nuclear ribonucleoprotein particle (snRNP) that contains seven Sm and three U1-specific RNP proteins-has a crucial function in the recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 18 publications
(24 reference statements)
2
41
0
Order By: Relevance
“…A similar process could also extend to anti-chromatin B cells in B6.NZBc13 mice. Although chromatin is a complex of DNA and histones that is recognized by DNA-sensing TLR9, it was recently shown to tightly associate with a complex of U1 RNA and another RNP, TAF15 [25]. As TLR3 and TLR9 are both sequestered in endosomes, chromatin-reactive B cells may also receive TLR3 signalling required for their activation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…A similar process could also extend to anti-chromatin B cells in B6.NZBc13 mice. Although chromatin is a complex of DNA and histones that is recognized by DNA-sensing TLR9, it was recently shown to tightly associate with a complex of U1 RNA and another RNP, TAF15 [25]. As TLR3 and TLR9 are both sequestered in endosomes, chromatin-reactive B cells may also receive TLR3 signalling required for their activation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…fus could ride with RNA polymerase II and either directly interact with the 59 splice site and recruit U1-snRNP to the nascent pre-mRNA or recruit other splicing factors. In this context, it is interesting that TAF15 has been shown to interact with the RNA component of U1, which provides direct interaction with the 59 splice site (Jobert et al 2009). The finding that a fus-binding motif (GGUG) closely resembles a consensus 59 splice site (GGUG/A) suggests a possible direct interaction with the 59 splice site.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that a chromatin-associated fraction of TAF15 associates with a human U1 small nuclear RNA. 8 Thus, we hypothesized that the U1-TAF15 particle is produced by remodeling of the canonical U1-snRNP, further suggesting a possible role of TAF15 in additional steps of RNA metabolism. Moreover, an interesting link between FET proteins and miRNAs has emerged.…”
Section: Taf15 (Formerly Tafmentioning
confidence: 99%